529. Systematic Review and Meta-Analysis of Ivermectin Safety Profile in COVID-19 Trials. (4th December 2021) - Wentzel, Hannah; Wang, Junzheng; Dayanamby, Abbienaya; Pilkington, Victoria; Levi, Jacob; Hill, Andrew; Ellis, Leah
Abstract: Background: There is a continued and pressing need for safe and effective treatment of COVID-19. Significant survival benefits have been shown by dexamethasone, tocilizumab and sarilumab, however they are only recommended in hospitalised COVID-19 patients. Ivermectin is a well-established and readily available antiparasitic drug which may be suitable for treatment in mild and moderate disease stages. It recently demonstrated anti-viral properties in vitro and now over 80 clinical trials have been registered worldwide to test its effectiveness in COVID-19 patients. This meta-analysis aims to collect data on adverse events reported in new COVID-19 treatment trials for the use of ivermectin as a repurposed medication. Methods: Data was extracted from randomised trials of COVID-19 treatment trials identified through systematic searches of PUBMED, EMBASE, MedRxiv and trial registries. The primary outcome of this meta-analysis is the frequency of adverse events. Key safety events included serious, gastrointestinal, neurological, cardiovascular and dermatological adverse events. Results: Overall, 18 trials investigating ivermectin for COVID-19 in a total of 2496 participants reported safety data and were included. There was no significant difference in the proportion of all adverse events between ivermectin and the comparator. There were 371/1261 (29%) adverse events recorded in the ivermectin containing arms and 376/1284 (29%) in the control arms (RR 1.02 [95% CI 0.77 - 1.34]; p = 0.91). There was no significant difference in the rate of serious adverse events across treatment arms (RR 1.95 [95% CI 0.75 - 5.11]; p = 0.18). No significant differences between ivermectin and the control were seen across different subcategories of adverse events. Figure 1 shows a summary of the results for all adverse events. Forest plot comparing ivermectin and the control for all adverse events in COVID-19 trials, subdivided into single-day dosing trials and multi-day dosing trials. Conclusion: The results of recent COVID-19 trials show that overall, ivermectin is safe and well-tolerated. No significant difference in adverse event reporting was found across all subgroups in single and multi-day treatment regimens for the studies analysed. Safety reporting methodologies often varied across trials. Future and ongoing trials should be encouraged to collect and monitor safety data systematically. Disclosures: All Authors : No reported disclosures